Biocatalytic Reduction of Formaldehyde to Methanol: Effect of pH on Enzyme Immobilization and Reactive Membrane Performance - Norhayati Abdul Rahman; Fauziah Marpani; Nur Hidayati Othman; Nur Hashimah Alias; Junaidah Jai; Nik Raikhan Nik Him (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Thermodynamic stabled CO2 molecules can be biocatalytically reduced to methanol via three cascade dehydrogenases (formate, formaldehyde and alcohol) with the aid of cofactor as the electron donor. In this study, Alcohol dehydrogenase (EC 1.1.1.1), the third step of the cascade enzymatic reaction which catalyzed formaldehyde (CHOH) to methanol (CH3OH) will be immobilized in an ultrafiltration membrane. The enzyme will be immobilized in the support layer of a poly(ether)sulfone (PES) membrane via a technique called fouling induced enzyme immobilization. The objective of this study is to evaluate the effect of varying pH (acid (pH 5), neutral (pH 7) and alkaline (pH 9)) of the feed solution during immobilization process of ADH in the membrane in terms of permeate flux, observed rejection, enzyme loading and fouling mechanism. The experiment was conducted in a pressure driven, dead-end stirred filtration cell. Reaction conversion and biocatalytic productivity will be also evaluated. The results showed that permeate flux for acid solution were the lowest during immobilization. High concentration polarization and fouling resistance cause lower observed rejection for pH 7 and 9. Enzyme loading for pH 5 give 73.8% loading rate which is the highest compared to 62.4% at pH 7 and 70.1% at pH 9. Meanwhile, the conversion rate during the reaction shows that reaction on fouled membrane showed more than 90% conversion for pH 5 and 7. The fouling model predicted that irreversible fouling occurs during enzyme immobilization at pH 7 with standard blocking mechanism while reversible fouling occurs at pH 5 and 9 with intermediate and complete blocking, respectively. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).